Fear of clowns: An investigation into the aetiology of coulrophobia - Tyson, Philip John; Davies, Shakiela K.; Scorey, Sophie; Greville, William James (Frontiers in Psychology, 2023)
Introduction Fear of clowns or coulrophobia is a little understood phenomenon despite studies indicating that it has a high prevalence in the general population. There have been no previous investigations into the aetiology of this fear, although several plausible hypotheses from the wider literature can be generated; the fear stems from media portrayals of scary clowns, from the unusual physical appearance or the unpredictable behaviour displayed, or it derives from an unpleasant personal experience. Methods The current study reviews the literature in this area and also pilots a new questionnaire (Origin of Fear of Clowns Questionnaire; OFCQ) to explore the causes of the fear of clowns in a sample of 528 participants who reported such a fear. Results Our findings suggest that uncertainty of harmful intent, media influences and unpredictability of behaviour play an important role in the origins of coulrophobia. There are also multiple features of clown appearance which produce a negative experiential state and a sense of a direct threat. Discussion We conclude that the origins of clown fear are multi-factorial and primarily relate to aspects of their facial appearance, their behaviour, and how they have been portrayed in the media. Surprisingly, fear derived from personal experience was not one of our main findings. Further research is focused on looking at associations between the level of fear and each aetiological category.